Challenges heirs faced in claiming inheritance property in Perak Tengah / Nabilah Syifaa bt Remy Rony and Nur Baizura bt Mohd Shukor - Remy Rony, Nabilah Syifaa; Mohd Shukor, Nur Baizura (2019)
Unclaimed inheritance property is still one of unresolved issues in Malaysia. It is pertaining to the accumulation of unclaimed asset over the years and become serious problem to the nation. The aim is to identify challenges from the heir’s perspective in claiming the inheritance property. In order to achieve this aim, three objectives are being set, namely: to identify the challenges heirs faced during the line chart of successor and their portion according faraid. The method use to obtain the data is by using quantitative analysis, and were analyze by using SPSS software. The questionnaire is given to the registered heirs under JKPTG Perak Tengah that comes for hearing session at Land Office in Seri Iskandar, Batu Gajah and Ipoh. The findings of this study is divided by 5 main factors, which is knowledge, procedures, costs, family problems and mentality. The result shows most heirs do not have understanding about the portion of each heirs therefore often leads to disputes among them. Thus, there is need to educate the heirs to be more concern about their actual roles in managing the deceased property administration.